IELTS Practice Test - Plus - Jackeman, Vanessa (Pearson Education, 2001)
IELTS stands for international English Language Testing System. It is a test of English language skills designed for students who want to study in the medium of English either at university, college or secondary school. There are two versions of the test: The Academic Module and the General Training (GT) Module. Students wishing to study at postgradute or undergraduate level should take the Academic Module.